Evaluation of Credit Worthiness for Institutional Financing through Growth of Populus deltoides Marsh Grown in forest Site and Farm forestry - Ramesh Singh, D. R.; Jhajaria, V. K. (Indian Forester, 2001)
Growth of Populus deltoides, Marsh Clone G-48 in enbloc, rainfed forest plantation and irrigated agroforestry situations in six villages of Yamuna Nagar District of Haryana State, India, was compared. Survival percentage in forest and farm land respectively was 34 and 80. MAI of forest plantation and weighted mean (Xw), of excellent, good and average categories of farmland respectively was 13.65 and 26.46 m3/ha/yr. respectively Wood harvesting cost was Rs. 643 and Rs. 660 per m3. The cost of formation was Rs. 31,450 and Rs. 2,16,000 per ha for rotation of eight years. Gross return from poplars grown on forest and farm land respectively was Rs. 32.756 and Rs. 85,308lha (Xw); net return respectively was Rs. 28,035 and Rs. 40,297/ha and Rs. 11,214 and Rs. 16,118/acre (0.4 ha). Farm inputs incidentally available are making inteqated farming a successful proposition. Loss of crop beyond forth year is leading to contractiOn of rotation. Forest plantations are managed under low intensity and institutional finance can be availed for raising poplars. Very fertile forest sites, with deep sandy soils and plentiful supply of good water are potential sites. High input and high output agroforestry should be selffinancing as accumulated interest after long rotation is deterring. Credit plans are to be made more flexible to allow shorter rotations as market acceptability of small size wood has increased. To sustain agroforestry revolution that earns an estimated Rs. 30 million/day (value added) diversification of Poplar clones and also other species is imperative, along with quality control of end product.